Diffuse Calcifications Protect Carotid Plaques regardless of the Amount of Neoangiogenesis and Related Histological Complications. (25th March 2015) - Vasuri, Francesco; Fittipaldi, Silvia; Pini, Rodolfo; Degiovanni, Alessio; Mauro, Raffaella; D'Errico-Grigioni, Antonia; Faggioli, Gianluca; Stella, Andrea; Pasquinelli, Gianandrea
Abstract : Background. Neoangiogenesis is crucial in plaque progression and instability. Previous data from our group showed that Nestin-positive intraplaque neovessels correlated with histological complications. The aim of the present work is to evaluate the relationship between neoangiogenesis, plaque morphology, and clinical instability of the plaque. Materials and Methods. Seventy-three patients (53 males and 20 females, mean age 71 years) were consecutively enrolled. Clinical data and 14 histological variables, including intraplaque hemorrhage and calcifications, were collected. Immunohistochemistry for CD34 and Nestin was performed. RT-PCR was performed to evaluate Nestin mRNA (including 5 healthy arteries as controls). Results. Diffusely calcified plaques (13/73) were found predominantly in females ( P = 0.017 ), with a significantly lower incidence of symptoms (TIA/stroke ( P = 0.019 ) than noncalcified plaques but with the same incidence of histological complications ( P = 0.156 ) ). Accordingly, calcified and noncalcified plaques showed similar mean densities of positivity for CD34 and Nestin. Nestin density, but not CD34, correlated with the occurrence of intraplaque hemorrhage. Conclusions. Plaques with massive calcifications show the same incidence of histological complications but without influencing symptomatology, especially in female patients, and regardless of the amount of neoangiogenesis. These results can be applied in a future presurgical identification of patients at major risk of developing symptoms.